Gender-Specific Adverse Effects of Mono-Ethylhexyl Phthalate on Steroidogenesis in Immature Granulosa Cells and Rat Leydig cell Progenitors in vitro - Svechnikov, Konstantin; Svechnikova, Irina; Soder, Olle (Frontiers in Endocrinology, 2011)
Di-2-ethylhexyl (DEHP) phthalate, one of the phthalates most widely distributed in the environment, causes reproductive toxicity that is attributable to the action of its primary metabolite, mono (2-ethylhexyl) phthalate (MEHP). Here, we have investigated the effects of MEHP on steroidogenesis by primary cultures of rat Leydig cell progenitors and immature granulosa cells. This phthalate stimulated basal steroidogenesis and StAR expression in both types of steroidogenic cells. However, when MEHP was incubated with (Bu)2cAMP, steroid production was increased in granulosa cells and suppressed in Leydig cell progenitors, a process associated with up-regulation of StAR expression. Our data suggest that MEHP exerts gender-specific adverse effects on the hormonal function of the developing gonads. This may be involved in the development of pathological conditions including disorders of prenatal sex development that may attenuate future reproductive health.